Structural, electrical properties and dielectric relaxations in Na+-ion-conducting solid polymer electrolyte. (28th March 2018) - Arya, Anil; Sharma, A L
Abstract: In this paper, we have studied the structural, microstructural, electrical, dielectric properties and ion dynamics of a sodium-ion-conducting solid polymer electrolyte film comprising PEO8 -NaPF6 + x wt. % succinonitrile. The structural and surface morphology properties have been investigated, respectively using x-ray diffraction and field emission scanning electron microscopy. The complex formation was examined using Fourier transform infrared spectroscopy, and the fraction of free anions/ion pairs obtained via deconvolution. The complex dielectric permittivity and loss tangent has been analyzed across the whole frequency window, and enables us to estimate the DC conductivity, dielectric strength, double layer capacitance and relaxation time. The presence of relaxing dipoles was determined by the addition of succinonitrile (wt./wt.) and the peak shift towards high frequency indicates the decrease of relaxation time. Further, relations among various relaxation times ( τ ε ′ > τ t a n δ > τ z > τ m ) have been elucidated. The complex conductivity has been examined across the whole frequency window; it obeys the Universal Power Law, and displays strong dependency on succinonitrile content. The sigma representation ( σ ″ v e r s u s σ ′ ) was introduced in order to explore the ion dynamics by highlighting the dispersion region in the Cole–Cole plot ( ε ″ v e r s u s ε ′ ) in the lower frequency window; increase in the semicircle radius indicates a decrease of relaxation time. This observation is accompanied by enhancement in ionic conductivity and faster ion transport. A convincing, logical scheme to justify the experimental data has been proposed.